Utilization of the metaverse in the context of interactive learning - Miftahul Khaira; Dimas Chandrasekha Lesmana; Putri Agustina; Dimas Saputra (Hipkin Journal of Educational Research, 2024)
In the rapidly developing digital era, the metaverse is increasingly becoming an integral part of human life, including in the world of education. Metaverse, as a three-dimensional virtual world, has great potential to change the learning paradigm into immersive and engaging interactive experiences. The use of the metaverse in interactive learning has become an interesting focus of exploration, along with advances in virtual reality and augmented reality technology. This opens the door to the exploration of new concepts through simulations, educational games, and global collaboration, freeing learning from the limitations of the conventional classroom. Engaging learning experiences, hands-on simulations in virtual environments, and global collaboration are the advantages of interactive learning through the metaverse. The literature review covers various types of metaverses, their potential in learning, their implementation in economic education, and interactive learning media based on Articulate Storyline 3. Although metaverses have a positive impact in improving the learning experience, ethical challenges such as accessibility, data security, and inclusivity need to be considered. The research results show that, although the metaverse opens a dynamic and exciting new era in digital education, certain limitations must be carefully addressed to ensure that the use of the metaverse in education provides maximum benefits for all students.   Abstrak Dalam era digital yang berkembang pesat, metaverse semakin menjadi bagian integral dari kehidupan manusia, termasuk dalam dunia pendidikan. Metaverse, sebagai dunia maya tiga dimensi, memiliki potensi besar untuk mengubah paradigma pembelajaran menjadi pengalaman interaktif yang mendalam dan menarik. Pemanfaatan metaverse dalam pembelajaran interaktif menjadi fokus eksplorasi yang menarik, seiring dengan kemajuan teknologi virtual reality dan augmented reality. Ini membuka pintu untuk eksplorasi konsep baru melalui simulasi, permainan edukatif, dan kolaborasi global, membebaskan pembelajaran dari keterbatasan ruang kelas konvensional. Pengalaman pembelajaran yang menarik, simulasi praktik langsung dalam lingkungan virtual, dan kolaborasi global menjadi keuntungan pembelajaran interaktif melalui metaverse. Tinjauan literatur mencakup berbagai jenis metaverse, potensinya dalam pembelajaran, implementasinya dalam pendidikan ekonomi, dan media pembelajaran interaktif berbasis Articulate Storyline 3. Meskipun metaverse memberikan dampak positif dalam meningkatkan pengalaman belajar, tantangan etika seperti aksesibilitas, keamanan data, dan inklusivitas perlu diperhatikan. Hasil penelitian menunjukkan bahwa, meskipun metaverse membuka era baru dalam pendidikan digital yang dinamis dan menarik, keterbatasan tertentu harus diatasi dengan cermat untuk memastikan bahwa penggunaan metaverse dalam pendidikan memberikan manfaat yang maksimal bagi seluruh peserta didik. Kata Kunci: media pembelajaran interaktif; metaverse; pembelajaran interaktif; transformasi pendidikan